Lease structures and occupancy costs in eco-labeled buildings. Issue 1 (4th October 2019) - Gabe, Jeremy; Robinson, Spenser; Sanderford, Andrew; Simons, Robert A.
Abstract : Purpose: The purpose of this paper is to investigate whether energy-efficient green buildings tend to provide net lease structures over gross lease ones. It then considers whether owners benefit by trading away operational savings in a net lease structure. Design/methodology/approach: Empirical models of office leasing transactions in Sydney, Australia, with wider transferability supported by analysis of office rent data in the USA. Findings: Labeled green buildings are approximately four to five times more likely than non-labeled buildings to use a net lease structure. However, despite receiving operational savings, tenants in net leases pay higher total occupancy costs (TOC), benefiting owners. On average, the increase in TOC paid by tenants in a net lease is equal to or greater than savings attributed to an eco-labeled building. Practical implications: A full accounting of TOC in eco-labeled buildings suggests that net lease structures provide numerous benefits to owners that offset the loss of trading away operational savings. Originality/value: The principal-agent market inefficiency, or "split incentive, " is a widely cited barrier to private investment in energy-efficient building technology. Here, a uniquely broad look at rental cash flows suggests its role as a barrier is exaggerated.